Telaah Dampak Boikot Produk Amerika terhadap Perekonomian Nasional - Sudarsono, Heri (Unisia, 2012)
A boycott plan of American products should consider national economy. The American products have contributed to the increase of national economic growth, because human and natural resource managements of Indonesia have depended on the American products. The boycott action would decrease economic growth, because it would decrease demands and increase unemployment. Besides, the action, on one side, would not be effective since economic relation between Indonesia and United States has been legitimized by both regional and international trade organization. On the other side, the dependency of Indonesia on American products have been relatively high, as seen from the volume of non oil and gas export-import between the two countries. Government economic policy is affected by cooperation with other countries, and therefore, the boycott action would not affect the decrease of consumption of American products. Keywords: boycott, economy, legitimacy, trade.